1981
DOI: 10.1073/pnas.78.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Muscle beta-actinin and serum albumin of the chicken are indistinguishable by physicochemical and immunological criteria.

Abstract: Chicken muscle ,B-actinin is considered to be one ofthe "true" myofibrillar components due to its specific binding to isolated myofibrils. Surprisingly, the direct comparison of this muscle protein with serum albumin, both isolated from chicken, showed that they behaved identically under several electrophoretic conditions. Furthermore, immunoreplica gels and doubleimmunodiffusion tests with antibodies prepared against 3-actinin established the serological identity of both proteins. No significant differences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In this regard, preliminary studies in this laboratory using pulse labeling with [3H]amino acids followed by immunoprecipitation with antisciatin IgG have demonstrated that mixed neuronal-glial cultures synthesize sciatin and that this synthesis is abolished by puromycin (Markelonis, Oh, Sofia, and Kim, unpublished data). Therefore, the relationship between sciatin and serum transferrin may be similar to that observed between avian muscle p-actinin and serum albumin, which were shown to be identical molecules by structural and immunological criteria (Heizmann et al, 1981). However, since monoclonal antibodies that do not cross-react with sciatin have been elicited against the serum factor (Oh, Cha, and Markelonis, unpublished data), these two proteins, although structurally very similar, may ultimately prove to be quite distinct.…”
Section: Discussionmentioning
confidence: 69%
“…In this regard, preliminary studies in this laboratory using pulse labeling with [3H]amino acids followed by immunoprecipitation with antisciatin IgG have demonstrated that mixed neuronal-glial cultures synthesize sciatin and that this synthesis is abolished by puromycin (Markelonis, Oh, Sofia, and Kim, unpublished data). Therefore, the relationship between sciatin and serum transferrin may be similar to that observed between avian muscle p-actinin and serum albumin, which were shown to be identical molecules by structural and immunological criteria (Heizmann et al, 1981). However, since monoclonal antibodies that do not cross-react with sciatin have been elicited against the serum factor (Oh, Cha, and Markelonis, unpublished data), these two proteins, although structurally very similar, may ultimately prove to be quite distinct.…”
Section: Discussionmentioning
confidence: 69%
“…14,15 The peak denaturation temperature of BSA using differential scanning calorimetry (DSC) is found at ∼60°C depending on the conditions used, 16 although the secondary structure starts to be lost permanently above 50°C. 17 The good gelation ability of BSA has long been established, 18 and it is known to form gels at <60°C.…”
Section: Thermal Stability Of Egg Yolk Proteinsmentioning
confidence: 99%
“…Chicken serum albumin (CSA) differs from both HSA and DSA in that it has glutamic acid at the third position [12]. This is due to an insertion in the protein sequence when compared with HSA, as opposed to the substitution observed in DSA.…”
Section: Introductionmentioning
confidence: 99%